The systematic investigation of tumors of the digestive tract by the system of pre staggered clinical investigation - Albot, Guy; Parturier de Albot, M; Bernard, Dr.; Legeron, Dr.; Dressler, Dr.; Prat, Domingo (Cirugía del Uruguay, 2020)
Presented at session 9th September 1953